Предмет: Математика,
автор: turganveliev
Решите уравнение
1). 2x + 5 = 2(- x + 1) + 11
2). 6y - 3(y - 1) = 4 + 5y
3). 4(x - 1) - 3 = - (x + 7) + 8
4). - 2(5x - 9) + 2 = 15 + 7(- x + 2)
5). 12 + 4(x - 3) - 2x = (5 - 3x) + 9
Ответы
Автор ответа:
1
Ответ:
2)6y-3(y-1)=4+5y
6у-3у+3=4+5у
3у-5у=4-3
-2у=1
у=-1/2=-0,5
3) 4x-4-3 = -x-7+8
4x+x = -7+8+4+3
5x = 8
x = 8/5
x= 1.6
4) -2(5х-9)+2=15+7(-х+2)
-10x+18+2=15-7x+14
-10x+7x=-18-2+15+14
-3x=9
-x=9/3
x=-3
5)12+4( х-3 ) -2х= ( 5-3х) +9
12+4x-12-2x=5-3x+9
4x-2x+3x=-12+12+5+9
5x=14
x=14/5
x=2.8
Пошаговое объяснение:
turganveliev:
а где 1? но всё равно спасибо
Похожие вопросы
Предмет: Русский язык,
автор: SenyaMiro
Предмет: Русский язык,
автор: vikatrebenok4
Предмет: Русский язык,
автор: 5555555512
Предмет: Математика,
автор: kamilla20099
Предмет: Қазақ тiлi,
автор: AlynaLoky